The effectiveness of role play method in enhancing english-speaking skills among secondary EFL learners - Ibnu Ziat Saragih; Farida Repelita Waty Br. Kembaren; Ernita Daulay (SCHOULID: Indonesian Journal of School Counseling, 2025)
This study examines the effectiveness of the role-play method in enhancing English-speaking skills among secondary EFL learners. Speaking skill constitutes a fundamental component of English as a Foreign Language (EFL) instruction, particularly at the secondary level where communicative competence is a primary learning objective. Nevertheless, many learners continue to experience difficulties in oral communication, including low self-confidence, limited vocabulary mastery, and insufficient opportunities for meaningful interaction, which are often associated with the predominance of conventional teacher-centered instructional practices, especially in religious-based educational settings. To address this issue, this study employed a quasi-experimental research design using a pretest–post-test control group approach. Participants were assigned to an experimental group and a control group. The experimental group was instructed using the role-play method, while the control group received conventional teaching instruction. A speaking performance test was administered as both a pretest and a post-test, and students’ speaking abilities were evaluated based on fluency, pronunciation, vocabulary, grammar, and comprehensibility. The collected data were analyzed using descriptive statistics and an independent samples t-test. The results indicated that both groups demonstrated comparable speaking abilities prior to the intervention. However, following the implementation of the role-play method, the experimental group showed a significantly greater improvement in English-speaking skills compared to the control group, with a statistically significant difference at the 0.05 level. These findings suggest that the role-play method is an effective instructional strategy for enhancing speaking competence and offers pedagogical implications for communicative-oriented EFL instruction, particularly within Islamic boarding school contexts.